STATISTICAL MECHANICS ANALYSIS OF THE ORDERING OF SI AND AL ATOMS IN ALBITE BY THE CLUSTER VARIATION METHOD - Abramovich M.G. (My University, 1987)
The temperature dependence of the distribution of Al and Si in tetrahedral positions in the feldspar lattice has been studied experimentally for a rather long time. Recent publications present a theoretical analysis of the problem based on a quasichemical approximation. The present paper proposes a more rigorous approach in which the cluster variation method is used to obtain the best self-consistent approximation of the combinatorial multipliers that define the entropy of the crystals. The theoretical analysis allows for local effective-charge balance.